Guidelines for community-based injury surveillance in rugby union. Issue 12 (December 2019) - Brown, James C.; Cross, Matthew; England, Michael; Finch, Caroline F.; Fuller, Gordon W.; Kemp, Simon P.T.; Quarrie, Ken; Raftery, Martin; Stokes, Keith; Tucker, Ross; Verhagen, Evert; Fuller, Colin W.
Abstract: Objectives: The vast majority of rugby union ('rugby') participants are community-based players; however, the majority of injury surveillance studies reported relate to the elite, professional game. A potential reason for this dearth of studies could be the perceived difficulty of using the consensus statement for injury recording at the community level. The aim of this study was to identify areas where the consensus statement could be adapted for easier and more appropriate implementation within the community setting. Design: Round-table discussion. Methods: All community-based injury surveillance issues were discussed during a 2-day facilitated round-table meeting, by an 11-person working group consisting of researchers currently active in rugby-related injury surveillance, sports medicine and sports science issues. The outcomes from the meeting were summarised in a draft guidance document that was then subjected to an extensive iterative review prior to producing methodological recommendations. Results: Each aspect of the rugby-specific consensus statement was reviewed to determine whether it was feasible to implement the standards required in the context of non-elite rugby and the resources available within in a community setting. Final recommendations are presented within a community-based injury report form. Conclusions: It is recommended that whenever possible the rugby-specific consensus statement for injury surveillance studies be used: this paper presents an adapted report form that can be used to record injury surveillance information in community rugby if suitable medical support is not available.